Literacy And Reward: Teachers’ Effort To Build Children Reading Habit - Helena Arisandi Komang Widia; Padmadewi Ni Nyoman; Artini Luh Putu (SHS Web of Conferences, 2018)
Children at early levels of primary school require appropriate guidance in their initial reading skill. They need to be trained on how reading becomes an enjoyable routine activity. This study aimed at describing teachers’ effort to build children reading habit. This study employed a qualitative descriptive study and conducted at North Bali Bilingual School Bali. The data were collected through observations and interview. The findings of the study showed that there were several activities conducted by the teacher as efforts to build children reading habit. In terms of building students’ reading habit, the teacher used (1) Point-written in Reading Rocket Chart (PRRC), (2) Chip (white, yellow, green) for appreciating good behaviour in reading and using English, (3) Certificate, (4) Class Reward, and (5) Free Play Time. With these efforts, it is evident that the students’ literacy improves and they exhibited great enthusiasm in their reading and studying literacy in the classroom.